Dynamics Of Adaptation Of The Plant Amorpha Fruticosa In The Conditions Of Karakalpakstan (Texas Journal of Multidisciplinary Studies, 2025)
The article presents the results of the dynamics of adaptation of the plant Amorpha fruticosa in the conditions of Karakalpakstan. Amorpha is a highly adaptable plant, which grows rapidly in the conditions of Karakalpakstan and is resistant to drought and salinity. In addition, during the cultivation process, we observed that the soil structure was good, and their salinity level decreased.